Role of Service Quality, Price Perception, Brand Image, and Information Technology Involvement in Banking Product Purchase Decisions - Prananta, Widya; Hapsoro, Bayu Bagas; Permana, Made Virma (JDM (Jurnal Dinamika Manajemen), 2021)
The decision to buy savings products at BRI is interesting to be raised in the research because, on the one hand, BRI is a bank that has a network of work units in remote areas of Indonesia so that it can serve the wider community, on the one hand, there are still many customers who complain about its services to BRI. This paper address the role of service quality, price perception, brand image, and purchase decision to banking products moderated by Information Technology. Data is collected through a questionnaire survey. This study employs purposive sampling to obtain respondents (n = 110), with the criteria, customers of the Britama account holder. Data analysis using SEM (Structural Equation Modeling) to get research results. Based on the results of confirmatory analysis and hypothesis testing, there is a strong relationship between the independent variables tested on the Purchase Decision of Britama Savings Products at BRI. Meanwhile, Information Technology moderated service quality shows a strong relationship. Price Perception with Information Technology moderation shows a weak relationship. Information Technology moderated Brand Image has no relationship with the purchase decision.